EFFECT OF CREDIT RISK MANAGEMENT ON FINANCIAL PERFORMANCE OF LISTED DEPOSIT MONEY BANKS IN NIGERIA - ABUBAKAR, NURUDDEEN; DADUM, HARUNA HAMZA; IBRAHIM, USMAN YAHAYA (Kashere Journal of Management Sciences, 2025)
This research investigates the effect of credit risk management on the financial performance of listed deposit money banks (DMBs) in Nigeria. Specifically, it focuses on analyzing the relationship between the non-performing loan ratio and financial performance, the connection between loan loss provisions and financial performance, and the link between the capital adequacy ratio and financial performance. The study utilized an ex-post facto research design, drawing data from the annual financial reports of 12 listed DMBs over a five-year period (2020-2024). Using regression analysis to evaluate the data, the findings revealed that the loan loss provision ratio (LLPR) has a positive and statistically significant relationship with return on equity (ROE), whereas ROE has a negative and significant impact on LLPR. Additionally, the results indicate a positive and statistically significant relationship between ROE and the capital adequacy ratio. Based on these findings, the study recommends that the Nigerian banking sector should closely monitor credit risk management indicators, as they are essential for assessing financial performance. Furthermore, to enhance the ROE of DMBs in Nigeria, management should consistently promote increased lending activities.